PENGARUH PROGRAM INOVASI JOJOBA (JUMAT OLAHRAGA, JUMAT OLAHRASA, JUMAT BAHAGIA) TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK - Kusumawati, Anik; Fajrie, Nur; Fathurohman, Irfai (Universitas Muria Kudus, 2024)
This research aims to measure the influence of school innovation on the formation of student’s character in increasing their belief in Almighty God, maintaining a healthy body by exercising, and caring for the environment. This is in accordance with the aim of the National Education System, namely to form the character of a generation that is dignified, has faith and trust in God, has good manners, is able to think creatively, has an independent spirit and has a sense of responsibility. JOJOBA school innovation is an innovation used at SMPN 1 batangan to strengthen the character of students. The research metod use qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. The result show that the student’s haracter is better than before, which has an impact on good school report cards.